2021
DOI: 10.1002/iub.2575
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the levels of exosomal miRNAs among human subjects could be explained by differential interactions of exosomes with the endothelium

Abstract: Exosomes are 30–100 nm endosome‐derived membrane vesicles, that contain specific RNA transcripts including mRNAs, and microRNAs (miRNAs) and have been implicated in cell‐to‐cell communication. Exosomal miRNAs in blood circulation have been attracting major interest as potential diagnostic and prognostic biomarkers in a variety of diseases including stroke, cancer, and inflammatory disorders. Despite the progress made in the utilization of circulating exosomal miRNAs as biomarkers for various human diseases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Significant limitations to introducing exosomal miRNA in real-world clinical practice must be mentioned. First, the methods to isolate exosomes are quite complex, and, to date, there is no standardization, making it difficult to compare and reproduce results, as also assessed by the high heterogeneity among studies [91]. It is critical to ensure standardized and reproducible methods for clinical translation.…”
Section: Discussionmentioning
confidence: 99%
“…Significant limitations to introducing exosomal miRNA in real-world clinical practice must be mentioned. First, the methods to isolate exosomes are quite complex, and, to date, there is no standardization, making it difficult to compare and reproduce results, as also assessed by the high heterogeneity among studies [91]. It is critical to ensure standardized and reproducible methods for clinical translation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we suggested that the differences in exosomal miRNA levels between patient samples and those from healthy individuals could stem from how exosomes containing c-miRNAs interact with endothelial receptors. These receptors tend to be more prevalent in states of disease, such as inflammation [ 154 ].…”
Section: Circulating Biomarkers: Is There An Ideal One?mentioning
confidence: 99%
“…Recently, we proposed that the observed variability in exosomal miRNA levels in patient samples compared to healthy individuals might be partly due to interactions between exosomes carrying c-miRNAs and endothelial receptors. These receptors are often overexpressed under pathological conditions such as inflammation [153].…”
Section: Weaknessesmentioning
confidence: 99%
“…Despite efforts to compare and optimize these methods, interlaboratory differences persist across isolation methods, yielding varied miRNA quantities and qualities (reviewed in [153]). For example, studies have found that TRIzol-based methods negatively impact RNA quality and that column-based methods are preferred.…”
Section: Weaknessesmentioning
confidence: 99%